2018
DOI: 10.22159/ajpcr.2018.v11s1.26614
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anticonvulsant Effect of Ethyl Acetate Fraction of Titanus Leaf (Leea Aequata L.) on Isolated Colon

Abstract: Objective: The excessive activity of the parasympathetic nervous system in the intestinal smooth muscle is important role in the increased intestinal motility, so antispasmodic medications are needed that can decrease intestinal motility such as atropine. Treatment may also use medicinal plants that are cheaper and easy to obtain, and also believed to have smaller side effects than modern antispasmodic drugs. This study aimed to determine the anticonvulsant or relaxation effects of the ethyl acetate fraction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Woode et al., (2011) reported that the aqueous extract of Leea guineensis leaves showed anticonvulsant activity [ 44 ]. The ethyl acetate fraction of Leea aequata leaves showed anticonvulsant effects on the colon contraction induced by acetylcholine [ 91 ]. In another study, it was reported that the ethanolic extract of Leea aequata leaves showed a significant relaxation activity against the smooth muscle contraction of isolated guinea pig trachea induced by acetylcholine [ 92 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Woode et al., (2011) reported that the aqueous extract of Leea guineensis leaves showed anticonvulsant activity [ 44 ]. The ethyl acetate fraction of Leea aequata leaves showed anticonvulsant effects on the colon contraction induced by acetylcholine [ 91 ]. In another study, it was reported that the ethanolic extract of Leea aequata leaves showed a significant relaxation activity against the smooth muscle contraction of isolated guinea pig trachea induced by acetylcholine [ 92 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Recent studies revealed that the seeds, stems and roots possessed antibacterial activity [7]. The leaves have anticonvulsant, antinociceptive and anthelmintic activity [28,31]. The L. aequata has widely been used by local practitioner against various diseases which encouraged us to carry out the pharmacological activity of this plant in this study.…”
Section: Introductionmentioning
confidence: 98%
“…Traditionally, the roots, tubers and stems are used as mucilaginous and astringent [30]. The barks and roots are used to treat indigestion, jaundice, chronic fever and malaria as astringent and anthelmintic [31]. The leaves and thigh are used as antiseptic and wound healing agent [30].…”
Section: Introductionmentioning
confidence: 99%
“…The roots, tubers, and stems are used as mucilaginous and astringents [ 32 ]. The bark and roots are used as astringents and anthelmintics, as well as to treat indigestion, jaundice, chronic fever, and malaria [ 33 ]. The roots, pounded with milk, are often prescribed for consumption; pounded with rice water, they are often prescribed for leukorrhea.…”
Section: Introductionmentioning
confidence: 99%